Unilateral abdominal bulging caused by L1-L2 herniation - Lima, Marco A. (2013)
Instituto Nacional do Câncer. Department of Neurosurgery., Rio de Janeiro RJ, Brazil / Fundação Oswaldo Cruz. Instituto de Pesquisa Clínica Evandro Chagas. Rio de Janeiro, RJ, Brasil.